Systems thinking, spirituality and wisdom: perspectives on Ken Wilber - Kamppinen, Matti (Approaching religion, 2015)
This is the editorial for the special issue 'Systems Thinking, Spirituality and Wisdom: Perspectives on Ken Wilber'.